Building research capacity to adapt and develop Patient-Reported outcome measures in low- and middle-income countries: results from a psychometrics workshop in Tanzania - Berivan Ece; Mrema Kilonzo; Sylvia Kaaya; Edith Tarimo; Candida Moshiro; Erasto Mbugi; Linda B. Mlunde; Lisa R. Hirschhorn; Claudia Hawkins; Emily H. Ho (BMC Health Services Research)
Abstract Background Effective antiretroviral treatment has transformed HIV into a manageable chronic condition. In Tanzania, about 1.7 million people are living with HIV (PLWH), with 79% achieving viral suppression. Patient-Reported Outcome Measures (PROMs) evaluate key outcomes that matter most for PLWH and are an essential tool to evaluate and improve health system performance. Research is needed to adapt and test PROMs to increase their use in HIV care in many low- and middle-income countries including Tanzania. Since 2019, Northwestern University and Muhimbili University of Health and Allied Sciences (MUHAS) have led an NIH-funded Fogarty D43 grant to build Patient-Centered Outcomes Research (PCOR) capacity in Tanzania. We report on the results of a workshop to strengthen capacity in PROMs development, adaptation and psychometric validation for improving health outcomes for PLWH in Tanzania. Methods The three-day in-person workshop featured expert-led instruction and practical exercises on PROMs selection, development, adaptation, validity testing, factor analysis, and manuscript writing. We applied Kirkpatrick Framework (Level 1-reaction, Level 2-knowledge, and Level 3-use) for workshop evaluation. Participants completed pre-workshop surveys on goals, experience, confidence, and knowledge, followed by a post-workshop survey to assess satisfaction (Level 1), knowledge changes (Level 2), and plans for use (Level 3), along with feedback. Results Twenty-seven participants (44.4% male) attended the workshop, with 92% stating it met workshop goals and 87.5% reporting personal goal fulfillment (Level 1). There was a significant increase in knowledge and confidence ratings across all topics (p <.001) (Level 2). Knowledge ratings rose from a mean of 0.44 (SD = 0.68) to 2.55 (SD = 0.56) while confidence increased from 0.47 (SD = 0.72) to 2.55 (SD = 0.56). Correct answer rates on knowledge assessments also improved and all attendees reported plans to use the skills in future research. Qualitative feedback indicated high enthusiasm for the course and increased confidence in applying the learned skills to current or future research (Level 3). Conclusions The workshop effectively strengthened capacity of attendees to adapt and validate PROMs for use in research and care in Tanzania. Plans are in place to incorporate this training into formal MUHAS courses. Similar workshops are needed to further enhance PROMs research capacity in the region for future application both in research and clinical care of PLWH.